Search for CP violation in D+s → K0Sπ+, D+ → K0SK+, and D+ → [psi]π+ decays - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Braun, Svende; Comerma-Montells, Albert; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2019)
A search for charge-parity (CP) violation in Cabibbo-suppressed D+s→K0Sπ+, D+→K0SK+, and D+→ϕπ+ decays is reported using proton-proton collision data, corresponding to an integrated luminosity of 3.8 fb−1, collected at a center-of-mass energy of 13 TeV with the LHCb detector. High-yield samples of kinematically and topologically similar Cabibbo-favored D+(s) decays are analyzed to subtract nuisance asymmetries due to production and detection effects, including those induced by CP violation in the neutral kaon system. The results are ACP(D+s→K0Sπ+)=(1.3±1.9±0.5)×10−3,ACP(D+→K0SK+)=(−0.09±0.65±0.48)×10−3,ACP(D+→ϕπ+)=(0.05±0.42±0.29)×10−3,where the first uncertainties are statistical and the second systematic. They are the most precise measurements of these quantities to date, and are consistent with CP symmetry. A combination with previous LHCb measurements, based on data collected at 7 and 8 TeV, is also reported.
Im Titel ist "psi" als griechischer Buchstabe dargestellt
Im Titel sind "+" und "0" hochgestellt, "s" ist tiefgestellt
LHCb Collaboration: R. Aaij, P. D'Argent, S. Bachmann, D. Berninghoff, M. Borsato, S. Braun, A. Comerma-Montells, M. Dziewiecki, D. Gerick, J. Grabowski, X. Han, S. Hansmann-Menzemer, J. Hu, M. Kecke, M. Kolpin, R. Kopecná, B. Leverington, H. Malygina, J. Marks, D. Mitzel, S. Neubert, A. Piucci, M. Schmelling, N. Skidmore, M. Stahl, S. Stemmle, U. Uwer, A. Zhelezov [und 818 weitere]
Gesehen am 28.05.2020